Prevalence and predictive factors of left atrial tachycardia occurring after second‐generation cryoballoon ablation of atrial fibrillation. (3rd November 2017) - Hermida, Alexis; Kubala, Maciej; Traullé, Sarah; Buiciuc, Otilia; Quenum, Serge; Hermida, Jean‐Sylvain
Abstract: Introduction: Assess the prevalence and predictors of left atrial tachycardia (LAT) after cryoballoon ablation of pulmonary veins. Methods and results: Patients who underwent catheter ablation of pulmonary veins with a second‐generation cryoballoon for symptomatic paroxysmal (151 of 270, 56%) or persistent (119 of 270, 44%) atrial fibrillation were entered in a single‐center prospective registry. Patients who experienced postcryoballoon LAT (pcryo‐LAT) were selected on the basis of 12‐lead ECG characteristics. Left atrial origin was confirmed during conventional EP study and electroanatomical activation mapping, and patients were treated by RF catheter ablation. Pcryo‐LAT was observed in 15 (5.6%) of 270 patients and was attributed to a reentrant mechanism in 11 patients (73%). The other four cases of pcryo‐LAT were due to focal atrial tachycardia associated with reconnection of one pulmonary vein. In comparison with patients who remained in sinus rhythm, LA area (HR = 1.09; CI 1.01, 1.2; P = 0.02), LVEF (HR = 0.94; CI 0.90, 0.97; P < 0.001), and LVEF <50% (HR = 8.5; CI 3.1, 23.6; P < 0.001) were predictors of pcryo‐LAT. After multivariate Cox analysis, only left ventricular ejection fraction < 50% remained predictive of pcryo‐LAT, (HR = 7.8, CI 2.3 26.7, P = 0.002). With a mean survival of 23 months, 73% of patients who experienced pcryo‐LAT were in sinus rhythm versus 78% of patients without pcryo‐LAT (log rank P = 0.85). Conclusion: The prevalence of pcryo‐LAT in patients with atrial fibrillation is low. Left ventricular ejection fraction < 50% is associated with an increased risk of pcryo‐LAT. When treated by RF catheter ablation, the presence of pcryo‐LAT is not a predictive factor of subsequent recurrence of atrial fibrillation during follow‐up.